Topic Management in Collaborative Oral Group Discussion of English as a Second Language Learners - Ezihaslinda, Ngah; Wan Jumani, Fauzi; Noor Raha, Mohd Radzuan; Noor Azlinda, Zainal Abidin; Amy Zulaikha, Mohd Ali; Fathiah Izzati, Mohamad Fadzillah; Hazlina, Abdullah (American Scientific Publishers, 2018)
This study investigates the management of topic in peer collaborative interaction in assessment context. The ability to manage discussion topic in a specific communicative event is fundamental to interactional competence. Topic initiation, topic expansion, moving from one topic to another as well as introducing new topics to peers during collaborative talk requires not only participants’ linguistic abilities but also active participation of all members. This study analysed oral group interactions of English as a Second Language Learners in an institution of higher learning in Malaysia. Group oral interactions of five groups from thirty students were transcribed and analysed using qualitative analysis software, Atlas.Ti. for thematic analysis. The topics used for the oral group discussion were part of compulsory assessments that the students had to undergo in order to complete the course. The findings show that the students were able to initiate the discussion, expand the topic at hand, provided agreement and disagreement where necessary in their effort to ensure the successful completion of the assigned task. The findings of the study have direct implications for language teaching and learning development especially where oral group interactional competence is concerned.